INDIKASI PRAKTIK DUMPING MENURUT KETENTUAN PERUNDANGAN INDONESIA - Putu Edgar Tanaya; Ida Ayu Sukihana (Kertha Negara : Journal Ilmu Hukum, 2013)
Indications Dumping Practices Legislation Provisions According to Indonesia. The existence of fuzzy norms in the explanation of Act No. 7 of 1974 on Ratification of the Agreement Establishing the World Trade Organization. This paper describes the indications that can be used to categorize an act into the practice of dumping pursuant to the laws of Indonesia. In addition, this paper also discusses the forms of dispute resolution pursuant dumping laws and regulations of Indonesia. In writing scholarly journals used this type of research is normative research. Indication of the existence of dumping of imported goods has seen the export price of the goods is lower than the normal value and import of goods. Dispute resolution developed in General Agreement on Tariff and Trade (GATT) done by non-litigation and litigation.